RESPON DUA VARIETAS KUBIS (Brassica oleracaeL.) TERHADAP BERBAGAI JENIS MULSA ORGANIK DI DESA LANGALESO KECAMATAN DOLO - Muhamad Ridwan; Rostiati Dg. Rahmatu; Ramli Ali (Universitas Tadulako, 2013)
The purpose of this study was to determine the effect of different varieties of cabbages and organic mulches on cabbage growth. The research was carried out in the Langaleso Village, District of Dolo from October to December 2012. This study used a Randomized Block Design in two factorial experiment. The first factor was the mulch consisted of control, rice husk, rice straw, and sawdust. The second factor was the variety of cabbage consisted of Grand 11 and Grand 22. There fore, there were 8 treatment combinations, each combination was repeated 4 times to obtain 32 unit experiments. The use of rice straw mulch resulted in better plant heightthan control, while the use of sawdust mulch produced larger leaf area and leaf number compared to control. The grand 11 varietyhad higher plant height at 22, 29, 36 and 43 days after plantingcompared to the 22 grand variety. The mulch additionand the cabbage variety showed no interaction effect on the growth of cabbage. Key Words : Cabbage, growth, mulching, and variety.